TEACHING COMPOSITION TO STUDENTS IN FINE ART EDUCATIONAL INSTITUTIONS AND DEVELOPING ARTISTIC AND CREATIVE THINKING AS A PEDAGOGICAL PROBLEM - Abdimominova Dildora (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
In the work of art, the scientific researches, methodical recommendations of foreign pedagogues and psychologists who have directly conducted research in this field are cited in the approaches to the issues of composition and the content, essence, pedagogical and psychological characteristics of its concept.